2016
DOI: 10.2135/cropsci2016.01.0009
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Scheduling Using Predawn Leaf Water Potential Improves Water Productivity in Drip‐Irrigated Cotton

Abstract: To address the effectiveness of predawn leaf water potential in plant‐based irrigation scheduling, Gossypium hirsutum L. plants were grown under fully irrigated and dryland conditions and under three predawn water potential (ΨPD) thresholds (−0.5, −0.7, and −0.9 MPa). Measurements included ΨPD, plant height, mainstem node number, lint yield, water productivity, and continuous crop canopy temperature. We found that ΨPD produced similar yields to current practices, while decreasing overall water use from 7 to 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 42 publications
1
31
1
Order By: Relevance
“…Regulated deficit irrigation (RDI) was a method developed by Mitchell et al (1984), which uses water deficits timed to particular crop growth stages in an effort to conserve water while avoiding yield losses typically seen in season-long deficit irrigation schemes. Fereres and Soriano (2007) demonstrated that RDI initiated during vegetative growth stages increased water productivity (agricultural product per unit of water supplied by rainfall and irrigation; Ali and Talukder, 2008;Chastain et al, 2016; also referred to as WUE by Whitaker et al, 2008) and producer profits when using deficits ranging from 60% to as high as 100% of evapotranspiration in fruit trees and vines). Fereres and Soriano (2007) demonstrated that RDI initiated during vegetative growth stages increased water productivity (agricultural product per unit of water supplied by rainfall and irrigation; Ali and Talukder, 2008;Chastain et al, 2016; also referred to as WUE by Whitaker et al, 2008) and producer profits when using deficits ranging from 60% to as high as 100% of evapotranspiration in fruit trees and vines).…”
Section: Assessing the Utility Of Primed Acclimation For Improving Wamentioning
confidence: 99%
“…Regulated deficit irrigation (RDI) was a method developed by Mitchell et al (1984), which uses water deficits timed to particular crop growth stages in an effort to conserve water while avoiding yield losses typically seen in season-long deficit irrigation schemes. Fereres and Soriano (2007) demonstrated that RDI initiated during vegetative growth stages increased water productivity (agricultural product per unit of water supplied by rainfall and irrigation; Ali and Talukder, 2008;Chastain et al, 2016; also referred to as WUE by Whitaker et al, 2008) and producer profits when using deficits ranging from 60% to as high as 100% of evapotranspiration in fruit trees and vines). Fereres and Soriano (2007) demonstrated that RDI initiated during vegetative growth stages increased water productivity (agricultural product per unit of water supplied by rainfall and irrigation; Ali and Talukder, 2008;Chastain et al, 2016; also referred to as WUE by Whitaker et al, 2008) and producer profits when using deficits ranging from 60% to as high as 100% of evapotranspiration in fruit trees and vines).…”
Section: Assessing the Utility Of Primed Acclimation For Improving Wamentioning
confidence: 99%
“…Variable rate irrigation (VRI) has been demonstrated to provide better water use efficiency (WUE) while increasing crop yields [4][5][6]. VRI systems are today integrated with a wide variety of information in order to define proper rates for each irrigation management zone (IMZ), ranging from soil moisture sensing to thermal imagery [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This method prevents water from being the limiting factor for cotton production systems in Georgia (Meeks 2013;Chastain et al 2014Chastain et al , 2016. However, from the physiologist's perspective, irrigation triggers that use the plant to sense its environment offer advantages over the water balance approaches discussed previously, because the cotton plant integrates soil, atmospheric, and plant factors so that the need for irrigation can be accurately determined from the water status of the plant (Jones 2007;Chastain et al 2014Chastain et al , 2016. Leaf water potential (Ψ l ) is a direct measure of the energy status of water expressed in units of pressure (Jones 2007).…”
mentioning
confidence: 99%